The Wild Silkmoths (Lepidoptera: Bombycoidea: Saturniidae) of Colombia: a database of occurrence points and taxonomic checklist - Jiménez-Bolívar, Andrea C.; Prada-Lara, Liliana; Laurent, Ryan A. St; Rougerie, Rodolphe (Zootaxa, 2021)
Based on the review of literature and biological collections, information retrieved from public online databases, and from fieldwork conducted between 2015 and 2020, we provide more than 3500 occurrence records and an updated checklist of Colombian Saturniidae, annotated with distribution data for all species. In the first checklist of Colombian saturniids published two decades ago, a total of 184 species were cited; in the current update the number has risen to 653 species/subspecies classified in 55 genera, representing all six recognized Neotropical subfamilies. The Andean and Pacific regions are the richest, accounting for about three quarters of all species listed herein. We call attention to the fact that for most speciose saturniid genera in the Neotropics, there remains a significant need for further taxonomic and systematic research with objective and integrative approaches. Likewise, it is necessary to continue the study of Saturniidae moths in Colombia, strategically increasing the sampling efforts in specific under-sampled natural regions to further document the diversity of this family in the country.